(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Studies have evaluated the prevalence of Autism Spectrum Disorders (ASD), focusing on different ages during childhood and adolescence. How cumulative prevalence increases before adulthood remains unclear. Methods: We used data from the Autism Register of the Regional Reference Centre for Autism in L’Aquila, Central Italy, to retrieve information on individuals born in 2001–2012 with any of the inclusion diagnoses of ASD (DSM criteria) for the period 2001 to 2018. Cumulative prevalence on L’Aquila district population data was calculated as percentages for three-year age strata. Results: All prevalence data were estimated at December 31st, 2018. The overall crude prevalence was 0.95% (352 cases over 36938 population). Cumulative prevalence was 1.19% among those born in 2001-2003 (15 to 17 years of follow up), 1.15% among those born in 2004-2006 (12 to 14 years of follow up), 1.04% among those born in 2007-2009 (9 to 11 years of follow up), 0.80% among those born in 2010-2012 (6 to 8 years of follow up), and 0.57% among those born in 2013-2015 (3 to 5 years of follow up). The proportion of ASD diagnoses until the age of 5 years, compared to the group diagnosed 6 to 8 years of age, showed a significant increasing trend over calendar time (53.6% for those born in 2001-2003, to 77.0% for those born in 2010-2012). Conclusions: Cumulative prevalence by time period provides a better understanding of ASD occurrence than a point prevalence. We did not find any difference in frequency of diagnosis comparing age strata and year of birth, suggesting that frequencies of ASD diagnosis remained roughly constant from 2001 to 2015. Results show that cumulative prevalence of autism diagnosis does not substantially change over time; instead, diagnosis of ASD is more likely at earliest ages over time, although new cases of ASD are also detected at later ages.